Activation of CHK1 in Supporting Cells Indirectly Promotes Hair Cell Survival - Jadali, Azadeh; Ying, Yu-Lan M.; Kwan, Kelvin Y. (Frontiers in Cellular Neuroscience, 2017)
The sensory hair cells of the inner ear are exquisitely sensitive to ototoxic insults. Loss of hair cells after exposure to ototoxic agents causes hearing loss. Chemotherapeutic agents such as cisplatin causes hair cell loss. Cisplatin forms DNA mono-adducts as well as intra- and inter-strand DNA crosslinks. DNA cisplatin adducts are repaired through the DNA damage response. The decision between cell survival and cell death following DNA damage rests on factors that are involved in determining damage tolerance, cell survival and apoptosis. Cisplatin damage on hair cells has been the main focus of many ototoxic studies, yet the effect of cisplatin on supporting cells has been largely ignored. In this study, the effects of DNA damage response in cochlear supporting cells were interrogated. Supporting cells play a major role in the development, maintenance and oto-protection of hair cells. Loss of supporting cells may indirectly affect hair cell survival or maintenance. Activation of the Phosphoinositide 3-Kinase (PI3K) signaling was previously shown to promote hair cell survival. To test whether activating PI3K signaling promotes supporting cell survival after cisplatin damage, cochlea explants from the neural subset (NS) Cre Pten conditional knockout mice were employed. Deletion of Phosphatase and Tensin Homolog (PTEN) activates PI3K signaling in multiple cell types within the cochlea. Supporting cells lacking PTEN showed increased cell survival after cisplatin damage. Supporting cells lacking PTEN also showed increased phosphorylation of Checkpoint Kinase 1 (CHK1) levels after cisplatin damage. Nearest neighbor analysis showed increased numbers of supporting cells with activated PI3K signaling in close proximity to surviving hair cells in cisplatin damaged cochleae. We propose that increased PI3K signaling promotes supporting cell survival through phosphorylation of CHK1 and increased survival of supporting cells indirectly increases hair cell survival after cisplatin damage.